Soul Flights - DeConick, April D. (Aries, 2017)
Narratives of soul flights are common in ancient Mediterranean literature, sharing many similarities such as the movement of the soul along a vertical path that is associated with life and death. But they also display significant differences such as peculiar accounts of cosmic realms, idiosyncratic reasons for soul flights, and wild diversity of associated rituals. Historical critical studies of soul flights have been unable to address successfully this problem of comparison, which remains unable to explain structures that are engineered consistently in cultural productions. Cognitive explanations are more helpful in this regard. Yet current cognitive explanations struggle to account for the differences. How can both the similarities and the differences be accounted for within the same parameters of the operations of human cognition? This paper presents a model called cognitive ratcheting to address this problem. It is a theoretical formulation of the natural mental process through which concepts take shape and are innovated when they are mentally mapped onto spatial orientations, then ratcheted up with intuitive cognition, and finally elaborated into many cultural variations by reflective thought. This process acknowledges that, at the same time a concept is diversified through reflective elaboration and ratcheted up within different cultural contexts, it retains deep structures, especially with regard to spatial orientations, intuitive processes, and reflective recursion.